2004
DOI: 10.2205/2003es000137
|View full text |Cite
|
Sign up to set email alerts
|

New paleomagnetic data for the Hauterivian-Aptian deposits of the Middle Volga region: A possibility of global correlation and dating of time-shifting of stratigraphic boundaries

Abstract: The aim of this project was to study the paleomagnetic stratigraphy of the Hauterivian-Aptian deposits in the Middle Volga region, namely in the areas of the Saratov, Samara, and Uliyanovsk right-hand Volga areas. Original data were obtained for the first time for the magnetic polarity of the Hauterivian and Barremian rocks of the Russian Platform. The results obtained for the Aptian rocks agree very well with the results of the previous paleomagnetic studies which had been carried out in the Uliyanovsk region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
3
0
3
Order By: Relevance
“…The magnetite was the main carrier of samples magnetization. Guzhikov et al [2003] the magnetization of these rocks was of orientational nature.…”
Section: Analyzed Materialsmentioning
confidence: 94%
“…The magnetite was the main carrier of samples magnetization. Guzhikov et al [2003] the magnetization of these rocks was of orientational nature.…”
Section: Analyzed Materialsmentioning
confidence: 94%
“…Êðîìå òîãî, ïîñêîëüêó íå âñå îòëîaeåíèÿ ïðèãîäíû äëÿ îïðåäåëåíèé íàïðÿaeåííîñòè ãåîìàãíèòíîãî ïîëÿ, òî íà ïðåäâàðèòåëüíîì ýòàïå èññëåäîâàíèé îñóùåñòâëÿåòñÿ èõ ðàçáðàêîâêà. Êðèòåðèè, ïî êîòîðûì ïðîâîäèòñÿ îòáîð îñàäî÷íûõ îáúåêòîâ, ïðèãîäíûõ äëÿ ðåêîíñòðóêöèé ïàëåîíàïðÿaeåííîñòè, ïîñòîÿííî ñîâåðøåíñòâóþòñÿ [King et al, 1983;Tauxe, 1993;. Guzhikov et al, 2003].…”
Section: ïðåäñòàâëåíî ÷ëåíîì ðåäêîëëåãèè â ã áàõìóòîâûìunclassified
“…Èçâåñòíû ðàçëè÷íûå ñèñòåìû òåñòèðîâàíèÿ, ïîçâîëÿþùèå ðàçëè÷àòü îñàäêè, îáëàäàþùèå ïðåèìóùåñòâåííî îðèåíòàöèîííîé ëèáî ïðåèìóùåñòâåííî õèìè÷åñêîé íàìàãíè-÷åííîñòüþ. Íàïðèìåð, ñîãëàñíî ðàáîòå [Guzhikov et al, 2003], îá îðèåíòàöèîííîé ïðèðîäå îñòàòî÷íîé íàìàãíè÷åííîñòè ñâèäåòåëüñòâóþò ñëåäóþùèå ïðèçíàêè: 1) íèçêàÿ ìåaeïëàñòîâàÿ êó÷íîñòü (äî íåñêîëüêèõ äåñÿòêîâ) è îáðàòíàÿ çàâèñèìîñòü âíóòðèïëàñòîâîé êó÷íîñòè îò ðàçìåðîâ ÷àñòèö îñàäêà, 2) íèçêèå çíà-÷åíèÿ ôàêòîðà Êåíèãñáåðãåðà ( ìåíüøå 0,1 ) , 3) íàëè÷èå îáëîìî÷íûõ çåðåí ìèíåðàëà íîñèòåëÿ îñòàòî÷íîé íàìàãíè÷åííîñòè. Ýòè òåñòû ìîãóò áûòü äîïîëíåíû.…”
Section: ïðåäñòàâëåíî ÷ëåíîì ðåäêîëëåãèè â ã áàõìóòîâûìunclassified
See 1 more Smart Citation
“…The results of separation of grains of magnetic minerals and thermomagnetic analysis suggested that terrigenic magnetite is the main carrier of the sediments magnetization (Bogachkin, 3 2004;Molostovskii et al, 2007). According to Guzhikov et al (2003) the following criteria indicate the orientational nature of the sediments' NRM and, hence, their primacy: the presence of detrital grains of ferromagnetic minerals, low values of the Königsberger factor (Q < 0.1) and low interlayer concentration of distribution of the vectors of remanent magnetization directions (k = 5 -15).…”
Section: Introduction Arxiv:physicsgeo-ph/mentioning
confidence: 99%